Analysis of Intron Sequences Reveals Hallmarks of Circular RNA Biogenesis in Animals - Andranik Ivanov; Sebastian Memczak; Emanuel Wyler; Francesca Torti; Hagit T. Porath; Marta R. Orejuela; Michael Piechotta; Erez Y. Levanon; Markus Landthaler; Christoph Dieterich; Nikolaus Rajewsky (Cell Reports, 2015)
Circular RNAs (circRNAs) are a large class of animal RNAs. To investigate possible circRNA functions, it is important to understand circRNA biogenesis. Besides human ALU repeats, sequence features that promote exon circularization are largely unknown. We experimentally identified circRNAs in C. elegans. Reverse complementary sequences between introns bracketing circRNAs were significantly enriched in comparison to linear controls. By scoring the presence of reverse complementary sequences in human introns, we predicted and experimentally validated circRNAs. We show that introns bracketing circRNAs are highly enriched in RNA editing or hyperediting events. Knockdown of the double-strand RNA-editing enzyme ADAR1 significantly and specifically upregulated circRNA expression. Together, our data support a model of animal circRNA biogenesis in which competing RNA-RNA interactions of introns form larger structures that promote circularization of embedded exons, whereas ADAR1 antagonizes circRNA expression by melting stems within these interactions.